The monetary and fiscal determinants of national savings in Pakistan: An empirical evidence from ARDL approach to co-integration - Imran Sharif Chaudhry; Umber Riaz; Fatima Farooq; Salyha Zulfiqar (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2014)
The objective of this paper is to discuss the short- and long-run relationships between national savings and its monetary and fiscal determinants in Pakistan, during the period 1972-2010. In this study, monetary determinants are M2, Deposit rate, Inflation rate and fiscal determinants are budget deficit, government expenditures, government savings and government revenue (taxation) of national savings. The bounds testing approach to integrated cointegration is used, which is applicable irrespective of whether the underlying variables are of order one or order zero. To estimate the short- and long-run elasticities, the autoregressive distributed-lag (ARDL) and error correction model (ECM) is used. The study concludes that deposit rate and government expenditures is showing positive relationship with national saving in both long run and short run. M2 is negatively related with national saving in long run but highly significant. Inflation rate is presenting a positive relationship with national saving in short run. The coefficient of government saving is larger in short run as compare to long run. No serial correlation exists in both models. Macroeconomic stability combined with solid prudential regulations of financial institutions may create an environment that will raise national savings.
Keywords: 330; national saving; fiscal; monetary; bounds testing; ARDL; ECM